ANALISIS PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN PADA PERUSAHAAN PENGOLAHAN DI KOTA SEMARANG - Manek, Daniel (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2013)
This research aimed to examine and measure the market orientation effects on marketing performance. The research sample was manufacture companies that constitutes of Small and Midlle Entrepreneurship in Semarang, particularly those which are customer of Bank Mandiri Business Banking Semarang – Gajahmada Branch. The manufacture companies sector in this research includes furniture, food & beverages, printing/ offset, machinery & workshop, garment & footwear, metal industry, plastic waste cycle, soapworks& cleansing ware and plywood. Number of respondent in this research concludes 105unit of companies, each company represented by their owner or manager. This research is using Structural Equation Modeling ( SEM) Analysis through AMOS 21.0 software. Based on the data analysis collected, it can be concluded that market orientation is positively and significantly affect the marketing performance. Moreover, the model developed in this study proved that: 1) Market orientation result also positively influence marketing performance through process of product adaptation and business strategy quality; 2) Business strategy and product adaptation has positive effect on competitive advantage; 3) Product adaptation and competitive advantage has positive influence to marketing performance.